Household Wastes as Larval Habitats of Dengue Vectors: Comparison between Urban and Rural Areas of Kolkata, India. - Soumyajit Banerjee; Gautam Aditya; Goutam K Saha (PLoS ONE)
Porcelain and plastic materials constitute bulk of household wastes. Owing to resistibility and slow degradability that accounts for higher residence time, these materials qualify as potential hazardous wastes. Retention of water permits these wastes to form a congenial biotope for the breeding of different vector mosquitoes. Thus porcelain and plastic wastes pose a risk from public health viewpoint. This proposition was validated through the study on the porcelain and plastic household wastes as larval habitats of Dengue vectors (Aedes spp.) in rural and urban areas around Kolkata, India. The wastes were characterized in terms of larval productivity, seasonal variation and a comparison between urban and rural areas was made using data of two subsequent years. The number of wastes positive as larval habitats and their productivity of Aedes spp. varied among the types of household wastes with reference to months and location. Multivariate analysis revealed significant differences in the larval productivity of the household wastes based on the materials, season, and urban-rural context. Results of Discriminant Analysis indicated differences in abundance of Ae. aegypti and Ae. albopictus for the urban and rural areas. The porcelain and plastic wastes were more productive in urban areas compared to the rural areas, indicating a possible difference in the household waste generation. A link between household wastes with Aedes productivity is expected to increase the risk of dengue epidemics if waste generation is continued without appropriate measures to limit addition to the environment. Perhaps, alternative strategies and replacement of materials with low persistence time can reduce this problem of waste and mosquito production.